Readings in account planning - Weichselbaum, Hart (Chicago: The Copy Workshop, 2008)
Origins. The Account planning revolution. Ideas: How advertising works. Tools: A review of qualitative methods. Future: Above and beyond advertising planning
Keywords: Planificación de Presupuesto